Trans-Saharan Africa in world history - Austen, Ralph A. (New York : Oxford University Press, 2010)
"During the heyday of camel caravan traffic--from the eighth century CE arrival of Islam in North Africa to the early twentieth-century bui lding of European colonial railroads that linked the Sudan with the Atl antic--the Sahara was one of the world's great commercial highways, bri nging gold, slaves, and other commodities northward and sending both ma nufactured goods and Mediterranean culture southward into the Sudan. Hi storian Ralph A. Austen here tells the remarkable story of an African w orld that grew out of more than one thousand years of trans-Saharan tra ding. Perhaps the most enduring impact of this trade and the common cul tural reference point of trans-Saharan Africa was Islam. Austen traces this faith in its various forms--as a legal system for regulating trad e, an inspiration for reformist movements, and a vehicle of literacy an d cosmopolitan knowledge. He also analyzes the impact of European overs eas expansion, which marginalized trans-Saharan commerce in global term s but stimulated its local growth. Indeed, trans-Saharan culture not on ly adapted to colonial changes, but often thrived upon them, remaining a potent force into the twenty-first century"--Provided by publisher.
"This book tells the story of an African world that grew out of more than one thousand years of trans-Saharan trade linking the Mediterrane an lands of North Africa with the internal Sudanic grasslands stretchin g from the Nile River to the Atlantic Ocean. It traces the early role o f the Sahara, the globe's largest desert, as a divider that separated t hese two regions into very different worlds. During the heyday of camel caravan traffic--from the eighth-century CE Arab invasions of North Af rica to the early-twentieth-century building of European colonial railr oads that linked the Sudan with the Atlantic--the Sahara became one of the world's great commercial highways. The most enduring impact of this trade and the common cultural reference point of trans-Saharan Africa was Islam. This faith played various roles throughout the region, as a legal system for regulating trade, an inspiration for reformist religio us-political movements, and a vehicle of literacy and cosmopolitan know ledge that inspired creativity--often of a very unorthodox kind--within the various ethno-linguistic communities of the region. From the mid-1 400s, European voyages to the coast of West and Central Africa provided an alternative international trade route that marginalized trans-Sahar an commerce in global terms but stimulated its accelerated local growth . Inland territorial conquest by France and Britain in the 1800s and ea rly 1900s brought more serious disruptions. Trans-Saharan culture, howe ver, not only adapted to these colonial and postcolonial changes but of ten thrived upon them to remain a living force well into the twenty-fir st century"--Provided by publisher.
1. Introduction to the Sahara: From Desert Barrier to Global Highway -- 2. Caravan Commerce and African Economies -- 3. Ruling the Sahara a nd Its "Shores" -- 4. Islam -- 5. Islamicate Culture -- 6. European Col onialism: Disruption and Continuity of Trans-Saharan Links.
Includes bibliographical references and index.
Keywords: Trade routes -- Sahara -- History; Sahara; Islam -- Sahara -- History; Sahara